Actions and interactions of IGF-I and MMPs during muscle regeneration. (November 2021) - Kok, Hui Jean; Barton, Elisabeth R.
Abstract: Muscle regeneration requires the coordination of several factors to mobilize satellite cells and macrophages, remodel the extracellular matrix surrounding muscle fibers, and repair existing and/or form new muscle fibers. In this review, we focus on insulin-like growth factor I and the matrix metalloproteinases, which are secreted proteins that act on cells and the matrix to resolve damage. While their actions appear independent, their interactions occur at the transcriptional and post-translational levels to promote feed-forward activation of each other. Together, these proteins assist at virtually every step of the repair process, and contribute significantly to muscle regenerative capacity. Highlights: Insulin-like growth factor I (IGF-I) is essential to coordinate muscle regeneration. The matrix metalloproteinases (MMPs) enhance cell migration. The MMPs remodel the extracellular matrix during regeneration. Feed-forward IGF-I and MMPs crosstalk exists during regeneration.